Outcome analysis of surgically treated Tendo Achilles rupture - Nageshwaram, Jambu; Ganesan, Ganesan Ram; Subburayan, Ramesh Babu (International Journal of Research in Medical Sciences, 2017)
Background:The spectrum of Achilles tendon ruptures includes both acute and chronic injuries. Treatment options include operative repair with postoperative immobilization, operative repair with accelerated rehabilitation using early weight bearing, as well as non-operative treatment. Many surgeons advocate early operative repair of the ruptured Achilles tendon, citing decreased re-rupture rates and improved functional outcome while some surgeons treat them conservatively. In this article we are going to analyse the midterm outcome of surgically treated Tendo Achilles rupture. Methods:Prospective study of thirty cases of surgically managed Tendo Achilles injury treated in Sri Ramachandra medical college and research institute, Chennai, from June 2011 to June 2014. All the patients were followed up completely. Patients were followed periodically at 6 weeks, 12 weeks, 6 months and then yearly. Minimum follow up period was 12 months and maximum follow up period was 42 months. We have evolved our own scoring system and named it as comprehensive SRMC scoring system and all patients were followed using the scoring system. Results:We had 84% good results, 10% fair and 6% poor results as per comprehensive SRMC scoring system. Conclusion: SRMC scoring system for Tendo Achilles is a comprehensive one. It is specific for Tendo Achilles rupture. It includes all parameter for successful scoring system .Surgical treatment of Tendo Achilles gives good results.